Higher greenspace exposure is associated with a decreased risk of childhood asthma in Shanghai – A megacity in China - Hu, Yabin; Chen, Yiting; Liu, Shijian; Tan, Jianguo; Yu, Guangjun; Yan, Chonghuai; Yin, Yong; Li, Shenghui; Tong, Shilu (Ecotoxicology and environmental safety, 2023)
Inconsistent evidence exists about whether exposure to greenspace benefits childhood asthma. Previous studies have only focused on residential or school greenspace, and no research has combined greenspace exposures at both homes and schools to determine their link with childhood asthma. A population-based cross-sectional study was conducted among 16,605 children during 2019 in Shanghai, China. Self-reported questionnaires were used to collect information on childhood asthma and demographic, socioeconomic and behavioural factors. Environmental data including ambient temperature, particulate matter with aerodynamic diameter less than 1 µm (PM1), enhanced vegetation index (EVI), and normalized difference vegetation index (NDVI) were collected from satellite data. Binomial generalized linear models with a logit link were carried out to evaluate the association between greenspace exposure and children’s asthma, as well as the effect modifiers. An interquartile range increment of whole greenspace (NDVI500, NDVI250, EVI500, and EVI250) exposure was associated with a reduced odds ratio of children’s asthma (0.88, 95% CI: 0.78, 0.99; 0.89, 95% CI: 0.79, 1.01; 0.87, 95% CI: 0.77, 0.99; and 0.88, 95% CI: 0.78, 0.99, respectively) after controlling potential confounders. Low temperature, low PM1, males, vaginal delivery, suburban/rural area, and without family history of allergy appeared to enhance the greenspace-asthma association. Increased greenspace exposure was associated with a lower risk of childhood asthma, and the association was modified by a range of socio-environmental factors. These findings add to the body of evidence on the benefits of biodiversity and supporting the promotion of urban greenspace to protect children’s health. •It’s the first study on whole greenspace near home and school and children's asthma.•Higher greenspace exposure was associated with lower risks of childhood asthma.•A range of socio-environmental factors modified the greenspace-asthma association.